Studies on predation of Prostephanus truncatus (Horn) (Col., Bostrichidae) and Sitophilus zeamais Mots. (Col., Curculionidae) at different densities on maize by Teretriosoma nigrescens Lewis (Col., Histeridae) - Ayertey, J.N.; Meikle, W.G.; Borgemeister, C.; Camara, M.; Markham, R.H. (Wiley, 1999)
Laboratory experiments using whole cobs were conducted to examine the effect of varying densities of the larger grain borer, Prostephanus truncatus and the maize weevil, Sitophilus zeamais on rate of population increase by the histerid beetle, Teretriosoma nigrescens, a predator primarily of P. truncatus. Densities of all species of insects were determined at the end of the experiment, and an electrophoretic analysis of gut content was conducted on larval and adult T. nigrescens sampled during the experiments. Results indicated that T. nigrescens has a strong preference for P. truncatus and densities of T. nigrescens were associated only with densities of P. truncatus. The maize weevil played little role as an alternative prey or in interfering with T. nigrescens reproduction.